Notice of Joint Meeting on November 19, 1998 and the Approval of Airport Noise Abatement Program and Policies - Rodney L. Murphy:::::: (1998)
The agenda for a joint meeting between Camarillo and Oxnard Airport Authorities. Includes a letter from Rodney L. Murphy discussing recommendations to help meet the goals of the Airport Authorities.